CFD anallysis on cost effective pico hydro turbine: A case study for low head and low flow rate condition - Masjuri , Musa; Juhari, Ab. Razak; Md Razali , Ayob; Mohd Afzanizam, Mohd Rosli; Safarudin Gazali , Herawan; Kamaruzzaman, Sopian (2011)
Pico-hydro turbine has been widely used for off-grid settlement especially for stand-alone domestic application. Jn most cases there is a trade-off between the flow rate and the available head. The fluctuation of water flow rate between wet and dry seasons obviously affected the performance of the turbine. The problem is compounded when a specific turbine is used in low head and low flow application. This paper discusses the performance of an axial-flow (propeller) turbine in this particular condition. Evaluation is made based on the blade parameters in order to improve its existing performance. Comparisons are made between the current blade and a modified version of it, in term of hub to tip ratio and the number of blades used. The values of hub to tip ratio ranging between 0.4 to 0.7. The numbers of blades used are 3, 4, 5, and 6. Simulation analysis was done using Computational Fluid Dynamics (CFD) software. Analyses were done on each of the turbine blade to find the optimum stream velocity and power output which can be derived for each combination of turbine parameters.The analysis results show that with lowest value of hub to tip ratio which is 0.4 and the lowest number of blades which is 3, contributed the best performance of the axial-flow turbine.